Prognostic Impact of Tumor Budding on Moroccan Gastric Cancer Patients - Souhaila El Yaagoubi; Meryem Zaryouhi; Soumaya Benmaamar; Fatima El Agy; Layla Tahiri El Ousrouti; Nawal Hammas; Hicham El Bouhaddouti; Zineb Benbrahim; Nada Lahmidani; Laila Chbani (SAGE Publishing, 2023)
Background: Tumor budding (TB) has been defined as an independent prognostic factor in many carcinomas like colon adenocarcinoma, but its prognostic impact on gastric cancer patients remains not well established. In the present study, we aimed to highlight the correlation of tumor budding with clinicopathological features and predict its survival outcomes in gastric cancer patients for the first time in the Moroccan population. Methods: This study was conducted on 83 patients who underwent surgery for gastric adenocarcinoma from 2014 to 2020. The patient's clinico-pathological characteristics were obtained from the pathological and clinical records of each patient. Tumor budding was assessed on HES slides, according to the 2016 International Tumor Budding Consensus Conference criteria. The association of tumor budding grades with categorical and continuous variables were respectively assessed by the χ 2-test and the unpaired t -test. Survival analysis was performed by the Kaplan-Meier method, the log-rank test. Results: Patients consisted of 65.1% of men and 34.9% of women with a median age of 61.2 years. Histologically, the majority of the tumors were adenocarcinoma (65.1%). Among all cases, 18.1% were classified as Bud1 (15/83), (27/83) 32.5% as Bud 2, and 49.4% (41/83) as Bud 3 grades. High-grade tumor budding (BUD 3) was found to be significantly associated with special clinicopathological features including older age ( P  = .02), unradical resection (R1/R2) ( P  = .03), and the presence of vascular invasion ( P  = .05), and perineural invasion ( P  = .04). Furthermore, tumors with high-grade tumor budding were significantly associated with a low rate of resected lymph nodes ( P  = .04) and advanced TNM stage ( P  = .02). Among all stages, high-grade tumor budding was correlated with shorter overall survival in univariate and multivariate analysis ( P  = .04). Patients with high-tumor budding had worse relapse-free survival compared with patients with low-tumor budding grade ( P  = .01). Conclusion: According to our study, the high-tumor budding grade was correlated with unfavorable clinicopathological features and poorer survival. The present study findings suggest that tumor budding should be considered in the treatment and prognosis of gastric cancer patients.